2014
DOI: 10.1093/jxb/eru105
|View full text |Cite
|
Sign up to set email alerts
|

Chilling and frost tolerance in Miscanthus and Saccharum genotypes bred for cool temperate climates

Abstract: SummaryTriploid Miscanthus hybrids have superior chilling tolerance across Miscanthus and Saccharum genotypes bred for cool temperate climates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 55 publications
(79 reference statements)
9
50
0
1
Order By: Relevance
“…These findings contrast with our study, where Giganteus showed lower F v /F m but also higher growth and photosynthesis than Goliath under chilling stress. Similarly, Friesen et al (2014) and Głowacka et al (2015) measured F v /F m on several Miscanthus genotypes after cold stress in the field. As expected, values tended to be lower in more coldsensitive genotypes, but in both studies, the genotypes were identified with relatively high F v /F m values and relatively low CO 2 -assimilation rates.…”
Section: Efficiency Of the Photosynthetic Apparatus Under Chilling Stmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings contrast with our study, where Giganteus showed lower F v /F m but also higher growth and photosynthesis than Goliath under chilling stress. Similarly, Friesen et al (2014) and Głowacka et al (2015) measured F v /F m on several Miscanthus genotypes after cold stress in the field. As expected, values tended to be lower in more coldsensitive genotypes, but in both studies, the genotypes were identified with relatively high F v /F m values and relatively low CO 2 -assimilation rates.…”
Section: Efficiency Of the Photosynthetic Apparatus Under Chilling Stmentioning
confidence: 99%
“…For example, Dohleman and Long (2009) concluded that M. × giganteus produces 59% more biomass than maize in the American Midwest because its growing season is ---substantially longer and it thus absorbs more radiation. Miscanthus can grow at lower temperatures than most other C 4 crops (Farage et al 2006, Friesen et al 2014, Głowacka et al 2014 and it is able to actively assimilate carbon at temperatures well below those tolerated by most other C 4 species (Long and Spence 2013). For example, the base temperatures for shoot emergence as determined by Farrell et al (2006) on four Miscanthus genotypes ranged between 6.0 and 8.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…data). Several studies have also shown that, although M. Âgiganteus '1993-1780' has higher growth and photosynthesis at temperatures below 14 C than other species in the tribe Andropogoneae, there is variation for these traits among and within Miscanthus species (Purdy et al, 2013;Friesen et al, 2014;Głowacka et al, 2014). Thus, a major goal of Miscanthus breeding is the production of biomass cultivars with improved cold hardiness and chillingtolerant photosynthesis.…”
Section: Introductionmentioning
confidence: 99%